Pediatric maxillofacial soft-tissue injuries: a retrospective analysis of 19,979 cases in a stomatology emergency department in southern China - Huihui Chang; Ye Yuan; Sixue Huang; Xin Chen; Xinmin Liao; Ge Yang; Guicong Ding; Chanchan Chen (BMC Oral Health)
Abstract Object The primary aim of this study was to review the demographic characteristics and treatments of maxillofacial trauma patients treated in the Oral Emergency Department of a hospital between 2016 and 2022. This study may serve as a reference for improving emergency healthcare systems and injury prevention in pediatric populations. Methods We searched the records of patients who were diagnosed with maxillofacial soft tissue trauma in the hospital information systems of Shenzhen Children’s Hospital. The extracted information included sex, age, diagnosis, duration of visits, medical procedures administered and associated cost. Results From 2016 to 2022, a total of 19,979 maxillofacial trauma patients, including 12,500 males and 7,479 females, were admitted to the oral emergency department. The average age of these patients was 49.13±29.83 months, with an average duration of visits lasting 53.12±85.13 minutes and an associated cost average of 460.33±332.91 CNY (approximately 63 USD) per patient. Patients aged 2 years composed the majority of the population. Lip injuries were the most prevalent, while chin injuries represented the most commonly treated type. Among the emergency trauma population, 13,288 (66.51%) patients required urgent surgical operation, while 3,693 (18.48%) patients required simple dressing alone. In addition, 2,998 (15.01%) patients required follow-up only. Conclusion Maxillofacial soft-tissue injuries, especially to the lips and chin, dominate pediatric oral emergency visits, which requires effective and timely management. Therefore, it is crucial for our society to put more concern on maxillofacial injury prevention.